Fiscal consolidation in Poland and it's economic consequences after the crisis 2008 - Mateusz Ciep±ucha (Journal of Contemporary Economic and Business Issues, 2016)
The paper focuses on public finance and the aspect of fiscal consolidation in Poland as economic consequences after the financial crisis in 2008. The study assumes that there is a wide range of needs for fiscal consolidation implementation in European post-crisis countries. Budgets of the vast majority of European Union Members are unbalanced, their deficits have a great, negative impact on the public finance sector, as well as on countries' GDP. The theoretical part presents a literature overview of the essence of consolidation and its role in fiscal policy. The empirical part of the paper focuses on trends, changes in the level of budget deficits in Poland and EU-27 and the influence of this on key macroeconomic indicators.
Keywords: E620; E62; E63; 330; balanced budget; deficit; fiscal policy; debt; public finance